Bronze electrodeposition from an acidic non-cyanide high efficiency electrolyte: tribological behaviour - Bengoa, Leandro Nicolás (2014)
Bronze coatings were electrodeposited onto a rotating cylinder electrode from a novel non-cyanide acid plating bath with high efficiency (92%). Deposits were obtained from a phenol sulfonic acid bath and their morphology, phase composition and tribological behavior were characterized. Cyclic and linear sweep voltammetries were used to study the effect of organic additives on the reduction processes to achieve an adequate formulation. The resulting bronze deposit consisted of a mono α-phase matrix with a 78% Cu and 22% Sn composition. Dry sliding wear tests were carried out employing a homemade ball on ring system and the coefficient of friction and wear resistance were quantified at different normal loads. Surface characterization of the bronze coatings showed that the resulting roughness is detrimental for the wear resistance of the deposit. This is evidenced by a higher friction coefficient and wear volume of Cu/Sn compared to a conventionally electrodeposited copper coating.